2010
DOI: 10.1159/000313530
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Adenovirus Activity of Epiandrosterone and Dehydroepiandrosterone Derivatives

Abstract: Background: Dehydroepiandrosterone (DHEA) exhibits a wide range of biological functions including antiviral activity. In this work, we present in vitro anti-adenovirus (AdV) activity of seven DHEA and twelve epiandrosterone (EA) analogues. Methods: The cytotoxic effect of the compounds was determined by the MTT assay and the antiviral activity by a virus yield inhibition assay. The mode of antiviral activity was examined using time-of-addition experiments, adsorption and internalization assays and Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 80 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Antiherpetic activity has been shown for aqueous plant extracts from Echinacea pallidum [32], Rumex acetosa [33] and Rhododendron ferrugineum [34], for polysaccharides derived from marine algae [35], for steroidal compounds against adenovirus [36] and an ethylacetate-soluble fraction from the lichen Ramalina farinacea against HIV [37]. Although all analyzed drugs in our study demonstrated virucidal activity, Melissa extract demonstrated a higher virucidal activity when compared to single compounds.…”
Section: Discussionmentioning
confidence: 62%
“…Antiherpetic activity has been shown for aqueous plant extracts from Echinacea pallidum [32], Rumex acetosa [33] and Rhododendron ferrugineum [34], for polysaccharides derived from marine algae [35], for steroidal compounds against adenovirus [36] and an ethylacetate-soluble fraction from the lichen Ramalina farinacea against HIV [37]. Although all analyzed drugs in our study demonstrated virucidal activity, Melissa extract demonstrated a higher virucidal activity when compared to single compounds.…”
Section: Discussionmentioning
confidence: 62%
“…The binding affinity between NAIs and neuraminidase as well as the route of NAI administration might explain the differences between the NAIs in the time taken for the alleviation of symptoms and fever. If NAIs had the same antiviral activities against influenza virus as DEAE affected adenovirus protein synthesis and mature particle formation [20], there was no difference in time between the alleviation of symptoms and fever. Further investigation is required to determine whether or not a rapid increase in the neuraminidase concentration from the start of medical intervention would be a more effective treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the lack of a secure and effective therapy against MV, research into finding new antiviral drugs is of great importance. Although DHEA has been attributed with many beneficial properties and antiviral activity against other viruses, the precise mechanism of action of DHEA remains unclear [41,48,49]. In this study we found that DHEA is active against MV in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 46%
“…This precise MTT procedure has been previously described [40] and the cytotoxicity of DHEA on growing cells was determined using the MTT assay described previously [41]. The compound concentration (碌M) that reduced cell viability by 50% of the control, calculated by regression analysis, was defined as CC 50 .…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%